Penerapan Metode Customer Satisfication Indeks (CSI) Dalam Pengukuran Tingkat Kepuasan Pasien Terhadap Pelayanan Kesehatan Di Rsud Hasanuddin Damrah Manna - Bima Dwi Cahya; Herlina Latipa Sari; Dimas Aulia Trianggana (Jurnal Media Infotama, 2024)
Hasanuddin Damrah Manna Regional General Hospital is one of the Regional General Hospitals in Bengkulu Province. So far, the Hasanuddin Damrah Manna Regional General Hospital already has a health service evaluation system based on the results of measuring the level of patient satisfaction, but the evaluation system is still manual in nature where the hospital distributes questionnaires to each patient to provide an assessment of satisfaction with the services provided by the hospital. Hasanuddin Damrah Manna Regional General Hospital. The application of the Customer Satisfication Index (CSI) method in measuring the level of patient satisfaction with health services at the Hasanuddin Damrah Manna Regional General Hospital can help the hospital in managing the results of assessing patient satisfaction with health services at the Hasanuddin Damrah Manna Regional General Hospital and can provide information results of measuring the level of patient satisfaction with health services at the Hasanuddin Damrah Manna Regional General Hospital as evaluation material to improve service quality. The application of the Customer Satisfication Index (CSI) method in measuring the level of patient satisfaction with health services at Hasanuddin Damrah Manna Regional General Hospital can be accessed online via the url link https://kepuasanrsudhasanuddindamrahmanna.my.id Based on the results of the demo program that has been carried out, 10 The respondent succeeded in providing an assessment of the application online using the respondent code that was obtained from the Hasanuddin Damrah Manna Regional General Hospital and the operator can also see the output of the satisfaction assessment results which will be given to the Head of the Hospital for evaluation. From the results of the assessment given by the 10 respondents, the results showed that the level of patient satisfaction with health services at the Hasanuddin Damrah Manna Regional General Hospital was Very Satisfied with a CSI (Customer Satifaction Index) value of 80.85%.